What about Bob? [videorecording (DVD)] - Oz, Frank; Murray, Bill, 1950 September 21-; Dreyfuss, Richard; Hagerty, Julie; Korsmo, Charlie, 1978-; Erbe, Kathryn (Touchstone Home Video : Distributed by Buena Vista Home Entertainment, 2000)
Bob Wiley, a troubled but lovable therapy patient, seeks help from noted psychiatrist Dr. Leo Marvin. When the doctor leaves town to go on a quiet family vacation, Bob, afraid of being alone, follows--showing up unexpectedly at the therapist's lakeside retreat. Bob becomes the houseguest that just won't leave.